Effect of vaginal progesterone in combination with cervical cerclage on improved gestational age and perinatal outcome in twin pregnancy: A prospective randomized study - N., Abdelaal; Z., Sanad; A., Shaheen; H., Hamza; A., Al Halaby (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Prematurity is the second leading cause of death in the first month of life. Objective of present study was to evaluate the effectiveness of vaginal progesterone and cervical cerclage each alone and in combination in improving gestational age in twin pregnancy and its subsequent impact on perinatal outcome. Methods: A sample size of seventy-five patients has been calculated out of those recruited from outpatient clinic at menoufia university hospital. All fulfilled eligibility criteria of having a twin pregnancy with a history of spontaneous preterm labour, or with a sonographic short cervical length <25mm in mid trimester. The participants were randomly assigned to three groups. Group 1 (N-25): received vaginal progesterone supplementation of 200 mg from 20 weeks until 34 weeks of gestation. Group2 (N-25): were remedied with cervical cerclage of Mc Donald type at 14-16 weeks of gestation Group 3 (N-25): received both vaginal progesterone as well as cervical cerclage. The primary outcome measure was spontaneous delivery between 34-37 weeks of gestation. Secondary outcomes were delivery prior 34 weeks of gestation as well as some parameters of neonatal morbidity and mortality. Results: There was a statistically significant higher gestational age in combination group when compared to progesterone group or cerclage group (P<0.001). Comparison between progesterone and cerclage groups did not reach statistical significance(P=-0.85). Both progesterone and cerclage groups demonstrated significantly lower birth weights, lower Apgar scores and a higher NICU admission rate than in combination group(P<0.001), while such significant difference did not exist between progesterone and cerclage groups. Conclusions: Combination of vaginal progesterone and cervical cerclage can improve gestational age at delivery as well as some parameters of perinatal morbidity and mortality in twin pregnancy.